Microstructure of modified asphalt with high desulfurized crumb rubber (DCR) contents and its impact on viscoelastic properties - Ruihuan Wang; Zhengkun Wang; Qingyuan Ma; Wenwen Yu; Fengbo Zhu; Hongwei He; Huayun Du; Lin Liao; Yinghua Fan; Bo Zhang; Qiang Zheng (Journal of Materials Research and Technology)
Desulfurized crumb rubber (DCR) derived from waste tires offers a sustainable solution for asphalt modification. While the performance of DCR-modified asphalt has been extensively investigated, the microstructure at high DCR contents remains poorly understood due to its inherent complexity. This study examined the structural evolution and viscoelastic properties of asphalt incorporating both low (10 % and 20 %) and high (30–45 %) DCR contents. At low contents, extensive DCR degradation led to dispersed island-like structures, whereas at high contents, reduced degradation resulted in a dual continuous phase characterized by macromolecular chain entanglement and network formation. This transformation enhanced elasticity, reduced sensitivity to temperature and frequency, and improved both high-temperature stability and low-temperature cracking resistance. Broadband dielectric spectroscopy revealed changes in molecular dynamics, including the disappearance of α-relaxation at high DCR contents, indicating restricted macromolecular chain mobility and further confirming the presence of a network structure. It is anticipated that understanding this structural difference with various DCR contents could promote the practical application of DCR-modified asphalt with high DCR contents, thereby advancing sustainability and economic efficiency.